Cell Assays: Surface‐Micromachined Microfiltration Membranes for Efficient Isolation and Functional Immunophenotyping of Subpopulations of Immune Cells (Adv. Healthcare Mater. 7/2013). Issue 7 (10th July 2013) - Chen, Weiqiang; Huang, Nien‐Tsu; Oh, Boram; Lam, Raymond H. W.; Fan, Rong; Cornell, Timothy T.; Shanley, Thomas P.; Kurabayashi, Katsuo; Fu, Jianping
<x xml:space="preserve">Abstract</x> An integrated microfluidic immunophenotyping platform is developed by Jianping Fu, Katsuo Kurabayashi, and co‐workers on page 965 for rapid and efficient isolation, enrichment, stimulation and functional immunophenotyping of subpopulations of immune cells. Such an innovative tool will allow comprehensive and systems‐level immunomonitoring to define and characterize the "immune status" of healthy individuals and patients, critical for clinical interventions and managements of patients with immune system disorders. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>